Mekanisme Transmisi Kebijakan Moneter Dalam Perekonomian Indonesia - Sinaga, Tresia Tiodora; Sudirman, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.08.TAHUN 2018DO - 10.24843/EEB.2018.v07.i08.p04, 2018)
This Thesis investigates the role of monetary transmission mechanism in Indonesia. The responses on leading indicator Indonesia economy to structural shock of Internasional dan domestic are estimated using monthly data of the open economy Structural Vector Autoreggression (SVAR) model approach. Block exogenous assumption on SVAR model and non-recursive zero restriction on AB model of contemporaneous matrix interaction of variables are imposing for SVAR model identification purpose. The estimation result reveal that Monetary Transmission Mechanism channels : interest rate, credit, exchange rate and assets price did not prove to be strongly effective play a crucial role in changes in financial market and good market. Further, we estimate crucial role of internasional shock and domestic shock using impulse response function and variance decomposition technique. This empirical investigation demonstrates result which more in line with the economic theory. However, result from the impulse response analysis show that price level rises and depreciation, not as expected. This thesis finds that Internasional shock have more a significant impact than domestic shock on Indonesia economy.